Solidarity. Selected essays - Gallin, Dan (London, 2014)
"A collection of 19 essays by Dan Gallin, the former general secretary of the Geneva-based International Union of Foodworkers (IUF). The essays include two autobiographical articles, three pieces from the late 1950s and early 1960s, and the remainder from the last two decades. Gallin writes about a broad range of issues including the Algerian revolution, the French Left, Victor Serge, Scandinavian social democracy, the international labour movement, domestic work, the informal sector and much more. Often controversial, always interesting, this is essential reading for social change activists, trade unionists and everyone on the left.